OHP-044 Active pharmacovigilance in the E. R.: MEREAFaPS project in Campania. (24th February 2014) - Ruggiero, F; Taurasi, F; Melillo, A; Russo, L
Abstract : Background: In 2010, the Campania Region joined the Multiregional Pharmacovigilance project called MEREAFaPS (Monitoring epidemiologic reactions and adverse events from medicines in emergencies) assigning one pharmacist to each of Avellino, Benevento and Salerno hospitals to carry out monitoring activities. Purpose: The main aim of the project was to increase reports of ADRs/ADEs through the constant and continued presence of the pharmacist in the Emergency Room (ER). His task, among other duties, was to spread the culture of pharmacovigilance among the medical staff. Materials and methods: The ADRs/ADEs detected were reported on a paper form, which also contained clinical information related to patient. The data collected were then sent, through a special computer application, to the Niguarda Cà Granda Hospital in Milan, national leader of the project, and then to AIFA (the Italian Medicines Agency). Results: The MEREAFaPS Project in Campania produced a total of 656 reports in 2010–2011. Specifically, the reactions involved 6 paediatric patients, 413 adults and 237 people over 65, of whom a majority were women. Approximately 38% of the ADR /ADE were 'Serious' (of which 15 endangered the patient's life and 233 had led to hospitalisation or a prolonged stay in hospital) and the remaining 62% were 'not serious'. In addition, 62 responses were assessed by the monitor-pharmacist as 'Avoidable'. Among the iatrogenic illness revealed, most involved skin and subcutaneous tissue reactions and gastrointestinal reactions, followed by systemic disorders and conditions related to the administration site. The medicines most involved were: amoxicillin/clavulanic acid (72 reports), acetylsalicylic acid (62) and warfarin (43). Conclusions: In the two-year period 2010–2011 the Campania MEREAFaPS project has contributed to a considerable increase in the number of reports of suspected ADR /ADE recorded in the AIFA's National Network of Pharmacovigilance from across the region. The Campania region generated the most national reports of the three Italian regions. No conflict of interest.